Development Of A Problem Based Learning Module To Improve Scientific Literacy Capability And HOTS On The Material Buffer Solution - Siringoringo, Debora Sevenia; Sugiharti, Gulmah (Jurnal Teknologi Pendidikan : Jurnal Penelitian dan Pengembangan Pembelajaran, 2025)
This research aims to determine the results of expert validation and student responses to problem based learning based modules on buffer solution material. The research was carried out at the Cinta Kasih Catholic High School, Tebing Tinggi City using a sampling technique, namely purposive sampling of 35 people. This type of research uses the Research and Development (R&D) research and development method with a 4D development model and research is carried out only up to the development stage. The research instruments that will be used in this research are validation sheets and questionnaires. The design of the module to measure students' level of scientific literacy and HOTS on buffer solution material is suitable for use with the results of expert validation of the module producing an average percentage value for content suitability of 90% with very high criteria. Meanwhile, student responses to the module were generated from the student response questionnaire sheet with the average percentage of student responses to the module obtained being 88%, including very high criteria, 27 students and 20% of students including high criteria (8 students). Based on student responses, it can be concluded that creating a module that aims to measure students' scientific literacy and HOTS regarding buffer solution material could be something more interesting, useful and interesting to use.